Comparison of Sensor Sensitivity to Cable Partial Discharge Phenomenon - Adi Nugraha; Efendi (Universitas Nusa Putra, 2022)
Partial discharge is a breakdown of the voltage caused by the inability of insulation to withstand the voltage. Partial discharge can occur on the inside. The surface of the insulation can even create arcs. PD modeling is proposed by experts and analyzed by mathematical models. Experiments for the presence of PD were carried out in 3 types, namely internal discharge, surface discharge, and tip discharge. Different results of PD intensity were obtained in each of these types. In this practicum, three experiments were carried out: calibration of the PD sensor, PDIV (Partial Discharge Inception Voltage), Background noise, and Waveform. So we get a value that can indicate the value and form of PD.